Reliability and methodology of quantitative assessment of harvested and unharvested patellar tendons of ACL injured athletes using ultrasound tissue characterization - Carla S. Pereira (14153325) (2019)
Ultrasound tissue characterization (UTC) imaging has been previously used to describe the characteristics of patellar and Achilles tendons. UTC imaging compares and correlates successive ultrasonographic transverse tendon images to calculate the distribution of four color-coded echo-types that represent different tendon tissue types. However, UTC has not been used to describe the characteristics of patellar tendons after anterior cruciate ligament reconstruction (ACLR). The aim of this cross-sectional study was to assess the intra and inter-rater reliability of the UTC in unharvested and harvested patellar tendons of patients undergoing ACLR. Intra and inter-rater reliability of both UTC data collection and analysis were assessed. Ten harvested and twenty unharvested patellar tendons from eighteen participants were scanned twice by the same examiner. Eleven harvested and ten unharvested patellar tendons from sixteen participants were scanned and analyzed twice by two different examiners. Twenty harvested and nineteen unharvested patellar tendons from twenty-three participants were analyzed twice by two examiners. Quantification of the proportion of echo-types I, II, III and IV in the areas of interest: (1) patella apex, (2) proximal tendon, (3) mid tendon, (4) distal tendon, and overall tendon of harvested and unharvested patellar tendons all displayed excellent intra-rater reliability (ICC2,1: 0.94 to 0.99), excellent inter-rater reliability for harvested and unharvested patellar tendon scanning and analysis (ICC2,1: 0.89 to 0.98), and excellent inter-rater reliability for analysis (ICC2,1: 0.95 to 0.99). Intra-rater reliability for the measure of volume was good (ICC2,1: 0.69 harvested, 0.67 unharvested), whilst mixed results were observed for the measure of mid tendon thickness (ICC2,1: 0.88 harvested, 0.57 unharvested). Inter-rater reliability for scanning and analysis was good for volume (ICC2,1: 0.67) and excellent for thickness (ICC2,1: 0.97), while the inter-rater reliability for analysis was fair to poor for volume (ICC2,1: 0.59 harvested, 0.30 unharvested), and excellent to poor for mid tendon thickness (ICC2,1: 0.85 harvested, 0.24 unharvested). UTC imaging is a reliable tool to characterize the quality of most aspects of unharvested and harvested patellar tendons in subjects undergoing ACLR. Other Information Published in: BMC Sports Science, Medicine and Rehabilitation License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1186/s13102-019-0124-x